Opportunities, Challenges and Strategies in Implementing Indonesian Health Insurance Scheme: Case Study at a Hospital Class C - Wiknjopranoto, Harie Moeljono; Nugraheni, Bernadia Linggar Yekti (Journal of Management and Business Environment (JMBE), 2024)
Research regarding the implementation of Indonesia Health Insurance patient services in hospitals has been conducted in previous studies.  However case study research regarding challenges, opportunities and strategies for implementing Health Insurance services in class C hospitals has been overlooked. This research aims to determine the challenges, opportunities and strategies carried out by Hospital X, a class C hospital, in serving Health Insurance patients so that it succeeds in optimizing its financial performance. Payment using the package system rates imposed by BPJS is both challenge and opportunity for hospitals that serve Health Insurance patients because this system is different from the fee for services payment system that is usually applied in hospitals. This research used a qualitative approach by conducting interviews with 8 participants at Hospital X. The data was analysed using the theory of institutional logics and institutional work. This research found the role of actors in the process of institutionalizing the Health Insurance system at hospital X as a reference for others hospital actors in assuring quality and cost control policies that can improve hospital financial performance.